Ouro de tolo: perspectivas de desenvolvimento em meio à globalização financeira - Watanabe, Daniel Takeshi [UNIFESP] (2019)
The aim of the present study is to articulate the changes that took place in the political economy of capitalism from the 1970s onwards to the lack of prospects for economic development in peripheral economies. The financialized way in which contemporary capitalism works and the hierarchical and asymmetric structure of the international financial and monetary system impose an external dimension that strongly conditions the insertion of emerging countries. It is intended, therefore, to expose the logical mediations and the factors exogenous factors linked to the difficulty of promoting development in these countries.